DUKUNGAN KELUARGA DALAM KEMANDIRIAN PERAWATAN DIRI ANAK RETARDASI MENTAL RINGAN DI SLB-C YKB GARUT - Yayu Eka Kartika; Ikeu Nurhidayah; Hendrawati (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Self-care is one of the important things that must be obtained by children of mental retardation, but there are still many families who do not provide support, emotional, informational, appreciation, instrumental, and social. The purpose of this study is to find out how family support that can be given to children with mild mental retardation in self-care independence in SLB-C Garut Karya Foundation (YKB). This study uses quantitative descriptive method, the population of all parents who have mild mental retardation children in SLB-C YKB Garut as many as 39 people, the sampling technique is a total sampling of 39 respondents, data collection using a family support questionnaire, with the validity test results obtained the results of r count 0.975 ? r table 0.444, and the results of the reliability Alpha Cronbach 0.980. The analysis used is univariate to describe the types of family support. The results showed that family support in children with mild mental retardation related to self-care independence around (51.3%), and families who did not support as much (48.7%). In research conducted at SLB-C YKB Garut shows that most families support, both in emotional support, informational support, appreciation support, social support and instrumental support. Therefore, with good support can help children mentally retarded to increase their independence. Intervention from nurses as health workers is needed to provide education to parents related to the support that must be given to children with mild mental retardation, to increase their independence in self-care